Implementation of Additive Weighting in Providing in Receiving Bidik Misi Scholarships at the Politeknik Bisnis Indonesia - Sahat Sonang Sitanggang; Andi Setiadi Manalu (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
This research was conducted to design a Decision Support System as a tool for decision makers in distributing the Bidik Misi Scholarship at the Politeknik Bisnis Indonesia. The selection of students who volunteered to become Bidik Misi Scholarship recipients used the Decision Support System (DSS) approach which applied the Simple Additive Weighting (SAW) method so that the decisions of Bidik Misi Scholarship recipients that had been subjective, non-transparent, and immeasurable could be overcome. The Simple Additive Weighting method is carried out by weighting the criteria and sub-criteria for each alternative for all attributes. The SAW method in the process is by normalizing the decision matrix (X) to a scale that can be compared with all existing alternative ratings. The criteria used in the SAW method in this study consisted of 2 (two) criteria and each of these criteria had Sub Criteria. The first criterion is Parents with Sub Criteria consisting of: Education, Income, The Number of Dependents. The second criterion is Students with Sub Criteria consisting of Age, Academic Potential, KIP Ownership. The output obtained from 5 data samples analyzed in this study obtained first rank NM1 with a value of 0.9, second rank NM3 with a value of 0.77, third rank NM5 with a value of 0.62, fourth rank NM4 with a value of 0.59, fifth rank NM2 with a value of 0.55. Based on the results of the tests conducted, it is concluded that the Bidik Misi Scholarship decision support system using the SAW method can make it easier and very helpful in solving the problems faced by the Politeknik Bisnis Indonesia.